2023
DOI: 10.1021/acsami.2c18691
|View full text |Cite
|
Sign up to set email alerts
|

MOF–Polymer Mixed Matrix Membranes as Chemical Protective Layers for Solid-Phase Detoxification of Toxic Organophosphates

Abstract: Zirconium-based metal–organic frameworks (Zr-MOFs) have been demonstrated as potent catalysts for the hydrolytic detoxification of organophosphorus nerve agents and their simulants. However, the practical implementation of these Zr-MOFs is limited by the poor processability of their powdered form and the necessity of water media buffered by a volatile liquid base in the catalytic reaction. Herein, we demonstrate the efficient solid-state hydrolysis of a nerve agent simulant (dimethyl-4-nitrophenyl phosphate, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…MOFs are a type of coordination compounds with network topologies that are extended by metal-linker coordination interactions. MOFs have gained much interest since their discovery as a type of organic–inorganic hybrid material with a variety of topologies. MOFs with high porosity structures can be designed in a variety of ways due to the versatile combinations of organic linkers and metal inorganic centers, distinguishing them from other nanoparticles such as carbon materials, zeolites, and porous silicon. This class of porous materials demonstrated distinct characteristics such as large specific surface area, open functional site, adjustable cavity, excellent thermochemical stability, tunable structures and functions, ordered pores, and large volume of pores. …”
Section: Introductionmentioning
confidence: 99%
“…MOFs are a type of coordination compounds with network topologies that are extended by metal-linker coordination interactions. MOFs have gained much interest since their discovery as a type of organic–inorganic hybrid material with a variety of topologies. MOFs with high porosity structures can be designed in a variety of ways due to the versatile combinations of organic linkers and metal inorganic centers, distinguishing them from other nanoparticles such as carbon materials, zeolites, and porous silicon. This class of porous materials demonstrated distinct characteristics such as large specific surface area, open functional site, adjustable cavity, excellent thermochemical stability, tunable structures and functions, ordered pores, and large volume of pores. …”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the exact mechanism in each step, data from several studies indicate that a catalytic reaction occurs in buffer solutions when both water and an exogenous base are present. ,,, The catalytic hydrolysis of OP nerve agents outside solution is less well supported, and the kinetics of this process are reported to be much slower than in solution. , Nevertheless, recent advances and modifications have yielded valuable insights that suggest a practical process may be possible. For instance, it was shown that the solid state reaction can be enhanced by selecting suitable Zr-MOFs, prewetting the adsorbent/catalyst, introducing structural features that enhance water adsorption within the MOF, and fortifying the structure with suitable bases. ,,, Furthermore, several techniques for integrating MOFs onto fibers or polymers suitable for use in air filtration or textile membranes have been explored. …”
Section: Introductionmentioning
confidence: 99%
“…Such micro-/nanoparticles might aggregate in the environment or natural ecosystems during the detoxication process and it is implausible to recover the adsorbents again. 22 Hence, it is highly desirable to hybridize such catalytically active MOFs with protective modules, such as cartridge lters, 23 selfstanding polymeric membranes, 24,25 packed column beads, 26 and wearable garments with applications as an effective real-time ltration entity. 27 Among these, the development of catalytically active MOF-impregnated fabrics, in combination with air permeability, gives rise to the self-detoxifying ltration fabric.…”
Section: Introductionmentioning
confidence: 99%